Implementation of quality management system by construction companies of the Republic of Guinea - Diallo, Aissatou Souelymane
Nowadays construction companies in the Republic of Guinea face many problems. The implementation of quality management system in construction companies is one of the performance methods that can overcome these problems. In the construction industry, a quality management system (QMS) could apply to all operations of the management function that define the quality strategy, goals, and obligations and execute them by means such as quality planning, quality monitoring, quality assurance, and quality enhancement within the quality system. Hence, the objectives of this research are to identify the practices of quality management system in construction companies, to identify the barriers that faced by construction companies and to develop the strategies for better implementation of quality management system to overcome the barriers in construction companies. This research adopted questionnaire survey to collect data. The data obtained from the questionnaire survey (38 no. of respondents) were analysed by using Statistical Package for Social Science (SPSS). From the result and findings obtained, it can conclude that all of the practices such as integrated project quality plan, process base management scheme, ;measurement of quality performance, specific skills or techniques, training programs for project staff, good team among project personal, well established communication channels for quality management and principle of continuous improvement to quality management are adopted by the construction companies, the barriers stated by most respondents faced by construction companies are lack of finance resources for quality management, poor use of quality management system as a marketing tool, lack of continuous improvement attitude for construction works and poor process management in construction projects. The most suggested strategies such as adopting modern technology to enhance quality in communication, training for project staff, create quality awareness among employees, educational programs for project staff, encourage employees to be creative, motivate project staff to participate in project quality management, construction companies to allocate sufficient human resources for quality management, construction companies to allocate sufficient finance resources for quality management, integrated project quality plan, measurement of company’s performance, government to enforce laws against corruption practices an implementation of process management are stated to overcome the barriers for better implementation of quality management system in construction companies in the Republic of Guinea.